Faithful imagination in the academy explorations in religious belief and scholarship - Curry, Janel M., 1956-; Wells, Ronald, 1941- (Lanham : Lexington Books, 2008)
In the past thirty years there has been a sea change in North American intellectual life regarding the role of religious commitments in academic endeavors. Driven partly by post-modernism and the fragmentation of knowledge and partly by the democratization of the academy in which different voices are celebrated, the appropriate role that religion should play is contested. Some academics insist that religion cannot and must not have a place at the academic table; others insist that religious values shoulddrive the argument. Faithful Imagination in the Academy takes an approach based on dialogu
Preface and Acknowledgments; Introduction; Part I. PROBING LINGUISTIC AND MORAL COHERENCE; Chapter 01. Words and Things: The Hope of Perspectival Realism; Chapter 02. Can We Be Good without God?; Part II. QUESTIONING ASSUMPTIONS UNDERLYING SCIENCE; Chapter 03. Can Scientific Laws Teach Us the Nature of the World?; Chapter 04. Design in Nature: What Is Science Properly Permitted to Think?; Part III. TRUTH TELLING AND TRUTH SEARCHING; Chapter 05. Reckoning with the Conquest of California and the West: Josiah Royce and American Memory1
Includes bibliographical references and index.
Description based on print version record.
Keywords: Theology -- Congresses; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Electronic books